P156 Outcome and Experience of Laproscopic Nissens Fundoplication in Adult Patients with Severe Asthma and Cough Who Have Gastroesophageal Reflux. (19th November 2012) - Ejiofor, S; Brebner, J; Barker, B; Mansur, A
Abstract : Introduction: Gastroesophageal reflux (GORD) is an important co-morbidity in patients with asthma. 1 It has a detrimental impact on symptoms with many patients being on oral corticosteroids despite maximal proton pump inhibitor (ppi) therapy. 1 Fundoplication in selected patients with severe asthma has been reported to improve asthma symptoms especially in children. 2 Birmingham Heartlands Hospital (BHH) is part of Heart of England NHS trust, one of the largest foundation trusts in UK. The Severe and Brittle Asthma Unit which operates from BHH has a policy of referring selected patients for Fundoplication. Method: In this prospective study all patients undergoing laparoscopic fundoplication were followed up for 12 months. All patients had GORD symptoms refractory to ppi therapy and proven reflux on oesophageal manometry. Prior to surgery and at 3 months patients symptoms were assessed with a) Mini asthma quality of life questionnaire (mAQLQ) b) Reflux Cough Questionnaire (RCQ)and c) Cough symptom Score (CSS). Lung function and medication were documented at follow up visits. Wilcoxon signed rank test was used in statistical analyses. Results: Between December 2009 and June 2012 13 patients underwent fundoplication. Patient characteristics are shown below. Fundoplication significantly improved CSS and RCQ at 3 months from baseline, p=0.002 and p=0.008 respectively. No significant change was seen in mAQLQ or lung function in asthmatic patients. Conclusions: Patients with severe cough and asthmatics with debilitating cough benefit from fundoplication. Asthmatics however have no significant improvement in quality of life scores or pulmonary function in the short term following fundoplication. References: Sontag et al A Am J Gastroenterol. 2003 May; 98(5):987–99. Rothenburg S et al J Pediatric Surg 2012 Jun; 47(6):1101–4.